A Throughput Analysis Using a Non-Saturated Markov Chain Model for LTE-LAA and WLAN Coexistence - Mun-Suk Kim (Mathematics)
To address the severe spectrum shortage in mobile networks, the 3rd Generation Partnership Project (3GPP) standardized Long Term Evolution (LTE)-License Assisted Access (LAA) technology. The LTE-LAA system ensures efficient coexistence with other existing unlicensed systems by incorporating listen-before-talk functionality and conducting random backoff operations similar to those in the IEEE 802.11 distributed coordination function. In this paper, we propose an analytical model to calculate the throughput of each system in a scenario where a single LTE-LAA system shares an unlicensed channel with multiple wireless local area network (WLAN) systems. The LTE-LAA system is utilized for supplementary downlink transmission from the LTE-LAA eNodeB (eNB) to LTE-LAA devices. Our proposed analytical model uses a Markov chain to represent the random backoff operations of the LTE-LAA eNB and WLAN nodes under non-saturated traffic conditions and to calculate the impact of the clear channel assessment (CCA) performed by the LTE-LAA eNB. Through numerical results, we demonstrate how the throughput of both the LTE-LAA and WLAN systems is determined by the contention window size and CCA threshold of the LTE-LAA eNB.